The Achmatowicz Rearrangement – Oxidative Ring Expansion of Furfuryl Alcohols - Deska, Jan; Thiel, Daniel; Gianolio, Eleonora (Synthesis, 2015)
Over the years, the oxidative ring enlargement of furfuryl alcohols, known as the Achmatowicz reaction, has been developed into a powerful and versatile synthetic tool for the preparation of 6-hydroxypyranones. This review provides a comprehensive collection of the various ways to perform Achmatowicz rearrangement reactions and explores the role of this ring-expansion process in contemporary organic synthesis.1 Introduction2 Classical Methods and Variants3 Single-Electron-Transfer Oxidations4 Metal-Catalyzed Ring Expansions5 Photolytic Oxygenations6 Enzymatic Transformations7 Conclusions
Keywords: Achmatowicz reaction; ring expansion; furan; pyranone; synthetic methodology; heterocyclic chemistry